Isolation and Identification of Effective Probiotics on Drug-Resistant Acinetobacter baumannii Strains and Their Biofilms - Zahra Abbasi; Seyed Mahdi Ghasemi; Yasaman Ahmadi; Dariush Shokri (Canadian Journal of Infectious Diseases and Medical Microbiology)
Introduction. This study aimed to identify, assess, and isolate strong lactobacilli demonstrating broad antibacterial and anti-biofilm activity against drug-resistant strains of Acinetobacter baumannii. Additionally, the mechanism of inhibition of these organisms was to be determined. Methods. Over a 6-month period (from December 2021 to June 2022), 53 clinical A. baumannii strains were collected from clinical samples. Twenty probiotic strains were isolated from local dairy products. Antibacterial activity of Lactobacillus strains’ cell-free supernatant (CFS) was identified using the agar well diffusion method and the microbroth dilution test. Anti-biofilm effect was performed by the microtiter plate assay. The MTT assay was also used to look into the probiotics’ cytotoxic effects on the L929 fibroblast cell line. Results. During the 6-month period, 53 clinical A. baumannii strains were obtained and identified. Out of 20 lactobacillus strains, the CFS of a lactobacillus strain (named L9) showed an inhibitory effect against all A. baumannii strains. Using the broth microdilution method, it was shown that the minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) of CFS extracts of L9 strains against A. baumannii strains were both ¼ mg/mL. The result of the anti-biofilm showed that the selected probiotic could inhibit biofilm formation. The most common organic acid produced by all Lactobacillus strains, according to the HPLC method, was lactic acid, which was followed by acetic acid. The L929 fibroblast cell line was used in the cytotoxicity assay, which revealed that 100% of the cells in the L929 fibroblast cell line survived treatment with successive doses of CFSs for a full day. Conclusion. The probiotic strain isolated from local yogurt in this study showed potential anti-biofilm and antimicrobial properties against all drug-resistant Acinetobacter isolates. Given the increasing interest in probiotic microorganisms based on their high health benefits, further studies are recommended on the mechanisms of action between probiotics and A. baumannii strains to find new solutions for biological control and treatment of these infections without the use of antibiotics.